WHAT HAPPENED TO THE FIRST SQUAD: A TRACER STUDY ON THE FIRST GRADUATES OF AN EARLY CHILDHOOD TEACHER EDUCATION DEPARTMENT IN CENTRAL JAVA INDONESIA - Waluyo, Edi (Indonesian Journal of Early Childhood Education Studies, 2013)
In 2007, Semarang State University (SSU) founded its Department of Early Childhood Teacher Education. The Department is also the first provider of degree level of preschool teacher education in the Province of Central Java Indonesia. Despite its young age, the Department has soon becomea reference institution at the provincial level. The Department, however, has been struggling for its curriculum improvement. This is partly also due to the fact that until 2007 there was only one degree-level preschool teacher education provider, for which curriculum evaluation seemed not anecessity. For the purpose of its curriculum improvement, the Department conducted a tracer study of its first alumni. It aimed to identify their personal and social acceptance and their role at the institutions they work for. The Department expected, based on the data on these matters, todevelop its curriculum, academic program, and institutional management improvement plans. 46 alumni teachers and 35 principals in whose centers the alumni work were involved. This study found that the alumni seemed to have no problem with their personal and social acceptance. Of those studied, 97.45% said to be confident with their ability in lesson planning and with their mastery of lesson contents. Most alumni also said that they have benefited from all courses, both the theoretical and the practical, they did during their university study, meaning that the Department curriculum is professionally relevant. Unfortunately, this was accompanied by a trend that no alumni offer alternative practice. In fact alternative practice is the very content the Departmentâs course on Curriculum Development they learnt. This could be because they are limited by the government regulation or by their centers they work for. Yet, somehow, from an academic point of view this is a daunting situation.